Pengaruh Emulsi Minyak Wijen dan Minyak Sereh sebagai Bahan Pelapis Jambu Biji Merah (Psidium guajava L.) terhadap Mutu selama Penyimpanan - Muhamad Ragil Zafansyah; Pande Ketut Diah Kencana; I Putu Surya Wirawan (Jurnal BETA (Biosistem dan Teknik Pertanian), 2025)
Red guava (Psidium guajava L.) is a climatic fruit that is quite recognizable. Red guava is a fruit whoseflesh is soft, quickly damaged and quickly decays. One of the efforts to minimize its damage and extendthe storage time of red guava fruit by using edible coatings made from sesame oil and lemongrass oilcoatings. The purpose of this study was to determine the effect of emulsion and find the bestconcentration on the coating material of a mixture of sesame oil and lemongrass oil. This study used acompletely randomized design (CRD) with two factorials. sesame oil concentration with levels (W)namely: 0%, 0.5%, 1% and lemongrass oil concentration (S), namely: 0%, 0.5%, 1% with 3 replications,therefore resulting in 27 experimental units. Perlakuan of 0.5% sesame oil concentration and 0.5%lemongrass oil (W1S1) is the perlakuan that produces the best value, namely the value of weight loss of19.15%, jumlah soluble solids 6.63 ºBrix, damage intensity 41.66%, fruit hardness 20.88%, andperlakuan of 1% sesame oil concentration and 0% lemongrass oil (W2S0) has the highest organolepticvalue of skin color, fruit flavor, fruit aroma, and fruit texture.